2017
DOI: 10.4236/ojog.2017.74044
|View full text |Cite
|
Sign up to set email alerts
|

Heme Iron Polypeptide in Iron Deficiency Anemia of Pregnancy: Current Evidence

Abstract: Iron deficiency is the most common nutritional deficiency leading to anemia in pregnancy. Conventionally, non-heme form of iron salts has been the mainstay of treatment. However, patient compliance is an important concern with existing oral iron therapy due to gastrointestinal side effects. Heme iron, a better bioavailable and tolerable form of iron can be suitable form of iron for supplementation in pregnancy. Evidence suggests its utility in pregnancy for treatment of iron deficiency anemia with benefits ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The maternally absorbed 58Fe tracer present in the neonates was significantly high compared to 57Fe tracer (2.7±1.3 versus 2.2±1.4; respectively). This suggests that the heme-iron has favorable transport through the placenta to the fetus (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternally absorbed 58Fe tracer present in the neonates was significantly high compared to 57Fe tracer (2.7±1.3 versus 2.2±1.4; respectively). This suggests that the heme-iron has favorable transport through the placenta to the fetus (21).…”
Section: Discussionmentioning
confidence: 99%
“…Abdelazim et al reported GIT intolerance/gastric upset in 1.7% (2/117) with HIP during the treatment of IDA with pregnancy (13). Pal et al, reported 4% poor compliance rate (<50% compliance) in the heme-iron treated group compared to 12% in the non-heme iron treated group(21).…”
mentioning
confidence: 98%
“…16 Compared to conventional oral irons, haeme iron polypeptide has seven times greater bioavailability and negligible side effects, and is postulated to be absorbed by dual mechanisms. 17,18 Gastrointestinal absorption of haeme iron is far less affected by dietary constituents such as polyphenolic tannins, phytates, and soy and dairy products (calcium). 15,16,19 This could have also supplement in the improvement of IDA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, heme-bound iron is recommended as the first choice of iron supplementation to treat IDA during pregnancy and to maintain maternal iron stores. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%